2019
DOI: 10.5944/rppc.23667
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del programa CIPRES sobre el riesgo suicida en adolescentes

Abstract: Effects of the CIPRES program on suicidal risk in adolescents. The objective of the study was to evaluate the specific changes generated by the CIPRES program on suicidal risk in adolescents. The sample comprised 106 adolescents aged between 13 and 18 years old (53 in the experimental group, 53 in the control group), of which 54.7% were women (n = 58). The study used a quasi-experimental design of repeated pretest-posttest measures with a control group. Two assessment instruments were administered before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
1
3
1
13
Order By: Relevance
“…Various research studies [ 8 - 10 ] have shown that one of the most important protective factors for mental health is social support, a paradoxical issue while in isolation, because isolation has specifically been studied as a risk factor, particularly for conditions linked to depression and suicide [ 11 ]. Thus, the psychological effects of quarantine include emotional disturbance, stress-induced depression, bad moods, irritability, insomnia, stress and posttraumatic stress symptoms [ 12 ].…”
Section: Quarantinementioning
confidence: 99%
“…Various research studies [ 8 - 10 ] have shown that one of the most important protective factors for mental health is social support, a paradoxical issue while in isolation, because isolation has specifically been studied as a risk factor, particularly for conditions linked to depression and suicide [ 11 ]. Thus, the psychological effects of quarantine include emotional disturbance, stress-induced depression, bad moods, irritability, insomnia, stress and posttraumatic stress symptoms [ 12 ].…”
Section: Quarantinementioning
confidence: 99%
“…Esta situación nos obliga a recomendar la realización de estudios epidemiológicos con protocolos unificados de tipo multicéntrico, con el fin de obtener tasas representativas en relación a los grupos de población investigados. De igual manera los programas de intervención, tanto a nivel terapéutico como preventivo, precisan de una mayor profundización y desarrollo (Bahamón et al, 2019). En sucesivas investigaciones sería recomendable poder incluir procedimientos que permitieran el seguimiento longitudinal y la evaluación de las intervenciones y de los resultados.…”
Section: Investigaciónunclassified
“…A study by Bahamón, Alarcón, García, and Trejos (2015) reported the relationship between maladaptive schemes and suicidal risk in 151 psychology students from Colombia. Approximately 75% of the sample showed a medium to high level of suicidal risk, while maladaptive schemes of emotional deprivation, abandonment, self-demandingness, distrust, and insufficient self-control positively correlated with suicidal risk.…”
Section: Introductionmentioning
confidence: 99%